DIGITALIZATION OF INDUSTRIAL ENTERPRISES: EVALUATION METHODOLOGIES AND OVERCOMING CHALLENGES - LYSAK, Viktor (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article highlights the pressing challenges and opportunities in the digitalization of resource and information flow management in industrial enterprises. The author emphasizes the necessity of creating comprehensive evaluation methodologies that incorporate both quantitative and qualitative aspects of digitalization. Key research areas identified include the application of modern technologies such as digital twins, the Internet of Things (IoT), blockchain, and machine learning methods. The article analyzes contemporary digitalization assessment methods, including quantitative, qualitative, modeling, and combined approaches, as well as their advantages, limitations, and areas of application. Particular attention is paid to evaluating tools that assess automation levels, digital maturity, and the economic impact of technology adoption.The author proposes new approaches to addressing key issues in digitalization evaluation, such as developing international standards to harmonize evaluation practices across industries and adapting digital indicators to enterprise strategies while considering environmental and social factors. Tools for small and medium-sized enterprises are suggested, including cloud platforms, mobile applications, and Open Source solutions for automated data collection and analysis. Significant attention is given to the integration of digital technologies into supply chains, operational activities, and human capital management.The research findings aim to establish a systematic approach to digitalization assessment that not only identifies bottlenecks in resource management but also promotes the development of innovative business models. Special emphasis is placed on the impact of digitalization on the efficiency, transparency, and flexibility of enterprises in a competitive environment. Future research directions include developing industry-specific digitalization standards, creating integrated data collection platforms, and studying the influence of digitalization on environmental sustainability, social responsibility, and competitiveness. Implementing the proposed solutions will enhance enterprises’ global economic positioning and foster the development of sustainable business models in the context of rapidly evolving digital technologies.
Keywords: digitalization; resource management; information flows; industrial enterprises; digitalization assessment; quantitative methods; qualitative methods; digital twins; Internet of Things; blockchain; sustainability; environmental impact; digital indicators; automation; digital maturity; competitiveness